New challenges to international marketing - Sinkovics, Rudolf R., 1966-; Ghauri, Pervez N., 1948- (Emerald, 2009)
Volume 20 of "Advances in International Marketing", guest-edited by Professors Sinkovics and Ghauri, addresses the impact on international marketing of major trends in the external and internal environment of the firm: technology-enabled international marketing research, environmental degradation, global warming; scarcity of resources, global account management, procurement and international supplier networks, internationalization of small and entrepreneurial firms, outsourcing and off shoring, and reliability and validity issues for construct measurement. The volume is organized in four sections. Section one presents a selection of papers that focus on the internationalization process of the firm. Section two combines studies with a small firm perspective and a focus on entrepreneurship. In the section on collaborative relationships, three studies examine value creation in strategic alliances, investigate reasons for international joint venture dissolution and offer a conceptual contribution on diversification - whether diversification results in a firm's value premium or a firm's value discount. The final section is devoted to methodological advancements. This section provides excellent examples of methodological challenges faced by today's scholars and managers alike.
Keywords: Export marketing -- Research.; elektronické knihy; electronic books